Recent global research and education : technological challenges : Proceedings of the 15th International Conference on Global Research and Education Inter-Academia 2016 /: technological challenges : Proceedings of the 15th International Conference on Global Research and Education Inter-Academia 2016. ([2017]) - Unknown
No abstract available